Radical nephrectomy with inferior vena caval thrombectomy for level I to IV tumor thrombus: long-term single-center experience - Navratil, Pavel; Chalupnik, Jiri; Louda, Miroslav; Habal, Petr; Zacek, Pavel; Brodak, Milos; Pacovsky, Jaroslav (BMC urology, 2025)
BACKGROUND: Renal cell carcinoma (RCC) is a prevalent kidney malignancy known for its aggressive nature and potential to extend into the renal vein or inferior vena cava (IVC), affecting patient prognosis and treatment strategies. OBJECTIVE: To assess the long-term outcomes and effectiveness of radical nephrectomy with IVC thrombectomy in patients with RCC presenting with level I-IV IVC thrombus. METHODS: A retrospective analysis was conducted on 164 adult patients treated for RCC with IVC thrombectomy at a tertiary care center from January 2004 to December 2023. Data including demographics, clinical characteristics, tumor specifics, surgical details, complications, and survival rates were meticulously reviewed. RESULTS: Among the patients, the mean age was 63.7 years, predominantly male (69.5%). The histological profile showed a majority of clear cell carcinoma (95.7%), with most tumors located on the right side (71.3%). Thrombus levels were distributed across I-IV, with 41 (25%) patients presenting with level I, 33 (20.1%) with level II, 55 (33.5%) with level III, and 35 (21.4%) with level IV thrombi. The mean operation time and blood loss increased with thrombus level. Perioperative complications were recorded in 57.3% of patients, and over half of the patients experienced disease recurrence (54.9%). The overall 5-year survival rate stood at 42.1%, with notably better survival in patients with level I thrombi. CONCLUSION: Radical nephrectomy with IVC thrombectomy provides a potential for long-term control in patients with RCC and IVC thrombus, although it is associated with significant morbidity. Multidisciplinary care and expert surgical intervention are crucial for improving patient outcomes. The variability in survival rates across thrombus levels underscores the need for individualized treatment approaches.
Keywords: dospělí; Female; Adult; výsledek terapie; ženské pohlaví; Venous Thrombosis; Radical nephrectomy; trombektomie; Time Factors; časové faktory; lidé; vena cava inferior; karcinom z renálních buněk; Treatment Outcome; Nephrectomy; Kidney Neoplasms; Carcinoma, Renal Cell; retrospektivní studie; Male; Aged; Inferior Vena Cava; Thrombectomy; Renal cell carcinoma; nádory ledvin; Vena Cava, Inferior; lidé středního věku; senioři; mužské pohlaví; Retrospective Studies; Middle Aged; žilní trombóza; nefrektomie; Humans